Black Heroism's Representation On Black Panthers Movie - Lintang Tavana; Budi Tri Santosa (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Most Hollywood production heroes come from western nations who are white, but not all heroes come from western countries, but some black heroes come from African nations. Marvel dares to raise a story with a background of black people as superheroes who managed to change the world's eyes that black people also have power over life in the world. This research has two objectives. First, analyzing the Black Panther film script is related to Black Heroism, a minority in the Hollywood film industry. Second, examine the elements of Black Heroism contained in the Black Panther film script to find out the aspects of Black Heroism. This research was conducted at the university using materials in the form of film script texts, films and academic books. The data collection technique in this study used library research, namely reading in-depth on the Black Panthers film script and marking and identifying data related to the research problem to be raised. This technique is used because the data source is written. The collected data is then analyzed using textual analysis or text analysis. It can be concluded that the character of the superhero in Marvel is different depending on the background of the superhero.